A Postmodern Theory of Industrial Democracy - Nodoushani, Omid; Nodoushani, Patricia (Journal of Comparative International Management)

(untitled) (Management Futures, 2000)
This paper argues that the greatly increased emphasis in our civilization today on expanding one of the oldest and most basic values, the idea of democracy, has given the public an interest in wanting more participation in the decision-making processes that vitally affect their welfare. It is the thesis of this paper that an extension of participative decision making into capitalism could develop what is called a postmodern theory of industrial democracy. At the same time, such a theory redefines the discourse on empowerment.